ACOUSTIC IMAGING, VISUALIZATION, AND QUANTIFICATION OF BUOYANT HYDROTHERMAL PLUMES IN THE OCEAN - Rona P.A.; Bemis K.G.; Silver D.; Jones C.D. (My University, 2002)
We develop and apply visualization and quantification methods to reconstruct hydrothermal plumes in 3D from acoustic images and to make the first direct measurements from the reconstructions of scalar properties that describe the behavior of two buoyant plumes discharging from adjacent black smoker chimneys. The actual behavior is then compared to that predicted by a classic simple buoyant plume model. The images are reconstructed as isointensity surfaces of backscatter from particulate matter suspended in the plumes. The measurements pertinent to the role of the plumes as agents of dispersal of heat and mass into the ocean include change with height of diameter, particle distribution, dilution, centerline attitude, surface protrusions, and connectivity. The protrusions are the surface expression of eddies and appear to follow a bifurcating helical flow pattern that resemble simulation of the naturally forced flow of coherent vortex rings as the eddies rise with the buoyant plume. These direct measurements and the derived entrainment coefficient are generally consistent with behavior predicted by the simple buoyant plume model and support engulfment by vortex shedding as a primary mechanism for entrainment of surrounding seawater. Deviations from predicted buoyant plume behavior are diagnostic of particle dynamics.